Answer:
Explanation:
Unfortunately it's not clear what you mean by 6 Σ 2 3(0.5)^n-1. I am going to assume that you mean summing up from n = 2 to n = 6 of the expression 3(0.5)^(n-1). Note that the "n-1" must be enclosed in parentheses.
a(2) = 3(0.5)^(2 -1) = 3(0.5) = 1.5
a(3) = 3(0.5)^(3 -1) = 3(0.5)^2 = 0.75
a(4) = 3(0.5)^(4 -1) = 3(0.5)^3 = 0.375
a(5) = 0.1875
a(6) = 0.09375
Sum these up to find the final answer.
If this is not what you expected, please start over: fix your formatting and put this problem into a new post.